PENGARUH NON PERFORMING LOAN (NPL) TERHADAP RETURN ON ASSSET (ROA) PADA PT. BANK MEGA, Tbk - Adea Nova Ramadhani; Puji Muniarty; Mukhlis (Lembaga Pengembangan Kinerja Dosen, 2026)
. Banks are anticipated to continue operating the business and enhance their performance if their Return On Asset (ROA) is high, since it calculates income and assesses the efficiency of the company's performance in using its assets. Examining how PT. Bank Mega, Tbk's Non-Performing Loans (NPLs) impacted ROA was the driving force behind this research. The study is an associative one. The research tool used is a collection of tables that include information from PT. Bank Mega, Tbk's balance sheet (total loans, non-performing loans, and assets), income statement (net profit, and assets), and research instrument (11 years, from 2014 to 2023). All of PT. Bank Mega, Tbk's financial reports covering the twenty-four years that the company was listed on the IDX (2000–2024) make up the study's population. This research uses PT. Bank Mega, Tbk's financial reports from 2014 to 2024 as its sample. This “research used purposive sampling as its sampling strategy. Documentation and literature review are the methods used to gather data for this investigation. Nonperforming loan (NPL) and return on asset (ROA) ratio analysis, simple linear regression, simple correlation coefficient, determination test, and t-test are some of the analytical methods used in this research. The analysis found that Non Performing Loans (NPLs) had a considerable impact on Return On Assets (ROA) at PT. Bank” Mega, Tbk.